Deletion of protein kinase B2 preserves cardiac function by blocking interleukin-6-mediated injury and restores blood pressure during angiotensin II/high-salt-diet-induced hypertension. Issue 4 (April 2018) - Yang, Shuai; Chen, Dandan; Chen, Fan; Zhao, Xinmei; Zhang, Yubin; Li, Zhe; Jin, Liang; Xu, Yitao; Sanchis, Daniel; Ye, Junmei
Abstract : Objective: Protein kinase B2 (AKT2) is implicated in cardiomyocyte survival during various stress conditions. However, the role of AKT2 in heart function, cardiac hypertrophy and blood pressure (BP) control during hypertension is not fully understood. Therefore, we sought to determine whether the deletion of AKT2 protects cardiac function during angiotensin II/high-salt-diet (AngII/HSD) treatment and find out the signaling pathway. Methods: Male C57BL/6J (wild type), AKT2 knockout and interleukin (IL)-6 knockout mice were fed a 4% NaCl diet for 5 weeks. In the last week, mice were split in two groups and infused subcutaneously with either vehicle or AngII (1.5 μg/h per mouse) for 1 week. Then, BP and cardiac function were assessed. Immunohistology of IL-6 and monocyte chemoattractant protein 1 was performed to detect inflammation in the heart. Masson's trichrome staining was performed to evaluate cardiac fibrosis. Heart tissue homogenates and neonatal mice cardiomyocytes were collected to analyze oxidative stress. Results: Compared with wild-type mice, AKT2 knockout mice maintained BP and showed better left ventricle ejection fraction, lower level of fibrosis, reduced oxidative stress, reduced IL-6 expression and less macrophage infiltration, when treated with AngII/HSD. IL-6 knockout mice treated with AngII/HSD also showed alleviated left ventricular function, fibrosis, oxidative stress and macrophage infiltration compared with wild type. Conclusion: AKT2 deficiency prevents the development of AngII/HSD-induced hypertension, cardiac dysfunction and myocardial injury including oxidative stress, fibrosis and inflammation by suppressing IL-6 expression. These data reveal an important role of the AKT2-IL-6 pathway in mediating AngII/HSD-induced hypertension and cardiomyopathy.